Role of CSR in Socio-Economic Development: A Case Study of Mahanadi Coalfields Limited (MCL), Odisha - Dehuri, Priyabrata; Bhua, Gopala (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Corporate Social Responsibility or CSR implies a strategic initiative that contributes to brand’s reputation. According to Archie Carroll, CSR can be understood as a pyramid of responsibilities namely; economic, legal, ethical& philanthropic framework aims to achieve societal objectives. The study generally explores how MCL’s CSR initiative contributes to sustainable development goals and integrating ethical practices by promoting social equity and environmental sustainability. The analysis highlights to know the impact of CSR activities in various areas such as poverty alleviation, employment generation, healthcare services and environmental conservation etc. By aligning corporate goals with the needs of communities and the environment, CSR enhances economic opportunities, promotes social inclusion, and mitigates environmental risks. The study addresses the role of CSR activities in socio-economic development and also explains the allocation of funds of MCL in various developmental activities of Odisha. To make comparative analysis various tools and techniques such as trend percentage, tables and graphs are used from data of five years i.e, FY 2018-19 to FY 2022-23 through secondary sources of information available from annual reports of MCL, Odisha. The study concludes that by adopting innovative and collaborative approaches, MCL’s CSR contribution can drive systemic change, balancing profit motives with their responsibility to society and sustainable development.